Human Embryonic Stem Cell-Derived Mesenchymal Stromal Cells Decrease the Development of Severe Experimental Autoimmune Uveitis in B10.RIII Mice. (17th November 2018) - Qin, Yu; Chan, Ann M.; Chang, Yu-Ling; Matynia, Anna; Kouris, Nicholas A.; Kimbrel, Erin A.; Ashki, Negin; Parikh, Sachin; Gorin, Michael B.; Lanza, Robert; Levinson, Ralph D.; Gordon, Lynn K.
ABSTRACT: Purpose : We investigated the effect of exogenously administered human embryonic stem cell-derived mesenchymal stromal cells (hESC-MSCs) in experimental autoimmune uveitis (EAU) in B10.RIII mice, a murine model of severe uveitis. Methods : B10.RIII mice were immunized with an uveitogenic peptide, and intraperitoneal injections of 5 million hESC-MSCs per animal were given on the same day. Behavioral light sensitivity assays, histological evaluation, cytokine production, and regulatory T cells were analyzed at the peak of the disease. Results : Histological and behavioral evidence demonstrated that early systemic treatment with hESC-MSCs decreases the development of severe EAU in B10.RIII mice. hESC-MSCs suppress Th17 and upregulate Th1 and Th2 responses as well as IL-2 and GM-CSF in splenocytes from hESC-MSC-treated mice. Conclusions : MSCs that originate from hESC decrease the development of severe EAU in B10.RIII mice, likely through systemic immune modulation. Further investigation is needed to determine any potential effect on active EAU.